Pembinaan Pemasangan Pembangkit Listrik Tenaga Matahari bagi Santri Dayah Mini Banda Aceh - Rakhmad Syafutra Lubis; Suriadi Suriadi; Mahdi Syukri; Ramdhan Halid Siregar; Masri Masri; Yuwaldi Away (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Solar energy is a renewable energy source that has become increasingly popular in recent years as an electricity source. However, the availability of trained personnel to install rooftop solar panels is limited. This community service program was conducted to provide training in residential solar system installation for students from Dayah Mini Banda Aceh. The training took place in the Power Electronics and Renewable Energy Laboratory at Universitas Syiah Kuala, where theoretical training on renewable energy was combined with demonstrations of equipment and simulated installation practice. The modules included rail mounting, panel positioning, inverter connections, charge controller setup, and wiring in series and parallel. Students were guided by lecturers and assisted by engineering students who had already undergone training in this field. They exhibited great enthusiasm and completed all the stages of installation successfully. This program not only addresses the shortage of workers with such skills in the solar installation industry but also helps students from low-income families acquire these practical competencies that can lead to jobs or entrepreneurship within the ever-growing sector of renewable energy; thus reducing unemployment among their communities while supporting Indonesia's shift towards sustainable energy.